Pembangunan kerjaya dalam organisasi bagi pekerja sokongan N9 : satu kajian di ibu pejabat Jabatan Perangkaan Sarawak di Kuching - Dayang Norelia, Binti Awang Julaihi (Universiti Malaysia Sarawak (UNIMAS), 2001)
Generally. this project aims to find out the relation between development and setbacks factors for carter development of workers in Sarawak Statistic Department headquarters at Kuching. This study is also conducted to determine the significant differences between chosen demographic factors such as age. gender and work experiences towards career development. Simple random sampling is used to collect data and the instrument used is a set of questionnaires, which were distributed to 50 rtspondents out of88 population consist ofN9 supporting staff. Descriptive statistic is used to analyze the background of the respondent. Independent T-test and One-way ANOVA is used to analyze the significant differences between demographic factors and career development. Pearson Correlation test was used to determine the significant relation between development and setback factors of career development in the organization. The outcome of this study shows that there is significant relation between organization and effort factors with career development whereby the value ofp<0.05. Based on the output. an opportunity and interest factor has a significant relevance with career development in the organization. There is also no significant difference between chosen demographic factors and career develDpment in the organization. Therefor, Sarawak Statistic Department should be more sensitive towards of development and setback factors of career development as well as the impact of these factor.f towards career development in organization to increase the effectiveness of the organization.